2011
DOI: 10.1111/j.1461-9563.2010.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weaver ants Oecophylla smaragdina on the shoot borer Hypsipyla robusta on African mahoganies in Australia

Abstract: 1 African mahogany Khaya senegalensis is a high-value timber tree species widely grown in central Africa, south-east Asia and northern Australia. Pilot plantings show that the tree grows well in the wet-dry tropical areas of northern Australia, and the shoot borer Hypsipyla robusta (Lepidoptera: Pyralidae) is a potential pest of the tree. The weaver ant Oecophylla smaragdina is an efficient biocontrol agent in some horticulture crops. To investigate whether the ants control shoot borers, field experiments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…In the present study, in the treatments without weaver ants, over 80% of trees at Berrimah Farm and 30-100% of trees at Howard Springs were attacked by fruit-spotting bugs (Table 1), and 10-65% of trees at Berrimah Farm and 10-52% at Howard Springs were attacked by Hypsipyla shoot borers (Peng et al, 2011b). robusta is essential.…”
Section: Discussionmentioning
confidence: 46%
“…In the present study, in the treatments without weaver ants, over 80% of trees at Berrimah Farm and 30-100% of trees at Howard Springs were attacked by fruit-spotting bugs (Table 1), and 10-65% of trees at Berrimah Farm and 10-52% at Howard Springs were attacked by Hypsipyla shoot borers (Peng et al, 2011b). robusta is essential.…”
Section: Discussionmentioning
confidence: 46%
“…As African mahoganies are widely distributed in tropical and subtropical African countries, and new plantations are heavily attacked by Hypsipyla shoot borers (Opuni-Frimpong et al 2008), it would be worthwhile conducting an assessment of the effects of local O. longinoda ants on the shoot borers and other pests on African mahoganies in tropical Africa. Peng et al (2011b) reported that O. smaragdina is an effective bio-control agent of Hypsipyla shoot borers on African mahogany trees in the Northern Territory.…”
Section: Discussionmentioning
confidence: 99%
“…Alexander). The impacts of fruit-spotting bugs and shoot borers and the control strategies have been reported (Peng et al 2011b(Peng et al , 2012. Although the damage caused by the yellow looper and bush crickets does not kill the trees, the resultant stem deformation reduces the production of timber (Peng et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being generalist predators, Oecophylla spp. can significantly reduce the abundance of several insect pests of tropical crops (Adandonon, Vayssières, Sinzogan, & Van Mele, 2009;Peng & Christian, 2004;Peng, Christian, & Gibb, 1995;Peng, Christian, & Reilly, 2011;Way & Khoo, 1989). Furthermore, Oecophylla ants are targeted as mini livestock for sustainable protein production, as they are used as food by humans and animals (Cèsard, 2004;FAO report, 2013;Offenberg, 2011;Sribandit, Wiwatwitaya, Suksard, & Offenberg, 2008;Van Itterbeeck, Sivongxay, Praxaysombath, & Van Huis, 2014).…”
Section: Introductionmentioning
confidence: 99%